(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
This article explores the impact of motivation on the English language proficiency of oil industry trainees in Saudi Arabia, with a focus on vocational and technical education contexts. Recognizing English as a critical tool for communication, safety, and technical operations in the oil sector, the study examines how various motivational constructs influence language learning outcomes through answering this research question: How motivational strategies can be used to enhance the language proficiency of oil industry trainees in Saudi Arabia? Drawing on key theories including Gardner’s Socio-Educational Model, Dörnyei’s L2 Motivational Self System, and Self-Determination Theory, the article analyzes different types of motivation (integrative, instrumental, intrinsic, and extrinsic) and their relevance to the vocational education settings. Scheidecker and Freeman (cited in Dornyei, 2001:1) point out that ‘motivation is, without question, the most complex and challenging issue facing teachers today.’ Accordingly, this study presents some pedagogical implications, emphasizing the importance of aligning instructional strategies with learners’ motivational orientations to enhance engagement and proficiency. Through a synthesis of theoretical perspectives and practical insights, the article highlights how motivation shapes language learning success and offers recommendations for improving English language instruction for vocational education trainees in Saudi Arabia.